How Does Culture Influence Student’s Assessments - Aihua Zhu (Forest Chemicals Review)
Many studies focused on variables affecting assessment such as different assessors and proper use of scales, few research focused on cultural factors. This study aims to explore how Chinese culture affects assessment results. Taking a writing assignment as a case study, it collected 100 students’ self-assessment and peer assessment scores, using a quantitative method to analyze their reliability. The result shows the inconsistency between different assessors. Face-to-face interviews are conducted, the findings indicate that some raters mark themselves higher to keep a high rank, for staying at the bottom is shameful. Peer assessments are mainly based on friendship, admiration, or maintaining harmonious interpersonal relationships. The results show that Chinese testing culture, face issues, relationship issues, the concept of harmonious coexistence, respect for labor, and worship of power have impacts on assessment behavior. Thus, assessments should take assessors’ social bonds and culture into consideration.